Enhanced osteogenesis and angiogenesis by PCL/chitosan/Sr-doped calcium phosphate electrospun nanocomposite membrane for guided bone regeneration. Issue 16 (2nd November 2019) - Ye, Huilin; Zhu, Junjin; Deng, Dan; Jin, Shue; Li, Jidong; Man, Yi
Abstract: Membranes play pivotal role in guided bone regeneration (GBR) technique for reconstruction alveolar bone. GBR membrane that is able to stimulate both osteogenic and angiogenic differentiation of cells may be more effective in clinic practice. Herein, we fabricated the Sr-doped calcium phosphate/polycaprolactone/chitosan (Sr-CaP/PCL/CS) nanohybrid fibrous membrane by incorporating 20 wt% bioactive Sr-CaP nanoparticles into PCL/CS matrix via one-step electrospinning method, in order to endow the membrane with stimulation of osteogenesis and angiogenesis. The physicochemical properties, mechanical properties, Sr 2+ release behavior, and the membrane stimulate bone mesenchymal stem cell (BMSCs) differentiation were evaluated in comparison with PCL/CS and CaP/PCL/CS membranes. The SEM images revealed that the nanocomposite membrane mimicked the extracellular matrix structure. The release curve presented a 28-day long continuous release of Sr 2+ and concentration which was certified in an optimal range for positive biological effects at each timepoint. The in vitro cell culture experiments certified that the Sr-CaP/PCL/CS membrane enjoyed excellent biocompatibility and remarkably promoted rat bone mesenchymal stem cell (BMSCs) adhesion and proliferation. In terms of osteogenic differentiation, BMSCs seeded on the Sr-CaP/PCL/CS membrane showed a higher ALP activity level and a better matrix mineralization. What's more, the synergism of the Sr 2+ and CaP from the Sr-CaP/PCL/CS membrane enhanced BMSCs angiogenic differentiation, herein resulting in the largest VEGF secretion amount. Consequently, the Sr-CaP/PCL/CS nanohybrid electrospun membrane has promising applications in GBR.